On Inspection of Hierarchical Inter-relationships Amongst Challenges Faced by Animal Food Manufacturers and Poultry Farmers in India - P.C Jha; Remica Aggarwal (Research Advances and Challenges in Agricultural Sciences Vol. 9, 2024)
The animal food industry has an animal pet population of about 29 million. On the other hand, animal husbandry deals with the care and breeding of livestock like buffaloes, cows, pigs, cattle, sheep, camels, goats, etc., When extended, it includes poultry farming and fisheries. The present paper tries to explore the challenges faced by the animal feed industry, animal husbandry and poultry farmers. It thereafter tries to explore the hierarchical inter-relationships amongst them using the VAXO technique of ISM methodology.